2020
DOI: 10.1038/s41598-020-73463-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-hematopoietic deficiency of proprotein convertase subtilisin/kexin type 9 deficiency leads to more severe anemia in a murine model of sickle cell disease

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) deficiency leads to lower cholesterol and is associated with reduced vascular complications in the general population. Cholesterol lowering may also have beneficial effects in sickle cell disease (SCD). The objective of this study was to determine effects of PCSK9 deficiency in a mouse model of SCD. Bone marrow transplantation (BMT) was performed from donor SCD mice to wild-type, PCSK9-deficient, and LDLR-deficient recipients to generate SCD controls (Pcsk9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Erythrocytes in blood extracted from SCD humans or mice undergo ex vivo sickling, which may be reflective of the in vivo sickling tendency 36,37 . Consistent with the reduced haemolysis observed in vivo following anakinra treatment, erythrocyte sickling in whole blood was reduced in anakinra‐treated mice.…”
Section: Discussionmentioning
confidence: 53%
“…Erythrocytes in blood extracted from SCD humans or mice undergo ex vivo sickling, which may be reflective of the in vivo sickling tendency 36,37 . Consistent with the reduced haemolysis observed in vivo following anakinra treatment, erythrocyte sickling in whole blood was reduced in anakinra‐treated mice.…”
Section: Discussionmentioning
confidence: 53%
“…BMP signi cantly decreased in PCSK9 −/−SCD erythrocytes To investigate mechanism(s) underlying the more severe anemia and hemolysis observed in SCD mice with and without PCSK9 de ciency [19] , erythrocytes collected from control SCD mice and PCSK9 de cient SCD mice underwent untargeted lipidomics analysis to test the hypothesis that PCSK9 may affect erythrocyte lipids. Of 543 lipid species analyzed, 11 lipid species were different between the 2 groups of mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Animals -Male C57BL/6J (Wildtype, Wt, stock # 000664), homozygous SCD mice (SCD, stock # 013071, Townes model) and PCSK9 −/− (stock # 005993) mice were purchased from Jackson Labs (Bar Harbor ME). Bone marrow was transplanted from SCD donor to PCSK9 de cient or WT recipient to generate the experimental PCSK9 −/− SCD bone marrow transplant (bmt) mice and the PCSK9 +/+ SCD bmt controls, as previously [19] . Lipidomics -Blood was drawn from the retro-orbital sinus of iso ourane-anesthetized mice (n = 3 per group) into 3.2% sodium citrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since HAMP is a major regulator of iron homeostasis and its levels are linked to different forms of anaemias, 53 the positive correlation between PCSK9 and HAMP expression also at steady‐state could have clinical implications. In fact, a recent study in mice demonstrated that non‐hematopoietic anaemia, independent of LDLR expression, was more severe in Pcsk9 KO mice 54 . It is important to note that conventional PCSK enzymes FURIN, PCSK5, PCSK6 and PCSK7 have been demonstrated to directly process pro‐hepcidin, 55 whereas FURIN has been reported to process PCSK9 56 .…”
Section: Discussionmentioning
confidence: 99%